The role of biodiesel in marine decarbonization: Technological innovations and ocean engineering challenges - D. Christopher Selvam; T. Raja; Beemkumar Nagappan; Vijay J. Upadhye; J. Guntaj; Yuvarajan Devarajan; Ruby Mishra (Results in Engineering)
The maritime sector, which contributes approximately 3 % to the total global greenhouse gas (GHG) emissions, is under increasing scrutiny to meet the decarbonization targets set forth by the International Maritime Organization (IMO) for the year 2050. Biodiesel, characterized by its renewable attributes and potential to diminish GHG emissions by as much as 80 %, emerges as a plausible alternative to traditional marine fuels. This research conducts a comprehensive analysis of the significance of biodiesel in the context of marine decarbonization, accentuating its benefits, which include reductions in Nitrogen oxide (Nox) emissions by up to 40 % and enhancements in fuel efficiency ranging from 3 % to 5 %, achieved through advancements such as nanoparticle additives and hybrid engine technologies. The study identifies challenges associated with biodiesel, including its 10 % to 12 % lower energy density and suboptimal cold flow characteristics, while proposing solutions that encompass innovative additives and thermal management strategies. The discourse further encompasses policy implications, logistical considerations of the supply chain, and the exploration of emerging feedstocks, notably algae-derived biodiesel. These insights establish biodiesel as a pragmatic, scalable, and ecologically sustainable fuel alternative for the maritime sector while delineating avenues to mitigate technological and operational challenges.